2013
DOI: 10.1103/physrevb.88.024418
|View full text |Cite
|
Sign up to set email alerts
|

Spin gap and the nature of the 4d3magnetic ground state in the frustrated fcc antiferromagnet Ba2YRuO6

Abstract: The geometrically frustrated double perovskite Ba2YRuO6 has magnetic 4d 3 Ru 5+ ions decorating an undistorted face-centered cubic (FCC) lattice. This material has been previously reported to exhibit commensurate long-range antiferromagnetic order below TN ∼ 36 K, a factor f ∼ 15 times lower than its Curie-Weiss temperature ΘCW = −522 K, and purported short-range order to T * = 47 K. We report new time-of-flight neutron spectroscopy of Ba2YRuO6 which shows the development of a ∼5 meV spin gap in the vicinity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 33 publications
10
61
1
Order By: Relevance
“…Analysis by x-ray powder diffraction showed a single phase product with a unit cell constant identical within statistical error with that reported. This sample is from the same batch as used in the inelastic neutron scattering experiments described previously 15 . A polarized neutron scattering experiment was carried out on the diffuse scattering spectrometer D7 at the ILL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis by x-ray powder diffraction showed a single phase product with a unit cell constant identical within statistical error with that reported. This sample is from the same batch as used in the inelastic neutron scattering experiments described previously 15 . A polarized neutron scattering experiment was carried out on the diffuse scattering spectrometer D7 at the ILL.…”
Section: Methodsmentioning
confidence: 99%
“…However, later neutron scattering studies including energy analysis, demonstrated that the (100) and (110) magnetic reflections remained resolution limited up to 47 K with a low incident energy and a narrow energy analysis window 15 . Upon widening the energy analysis window, the data more closely resembled those of the original diffraction experiments.…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, similar spin gaps in the long-range magnetic ordered state were observed in 3d 30) and other 4d electron systems. [31][32][33] …”
Section: (A)mentioning
confidence: 99%